2004
DOI: 10.1007/s10067-004-0867-x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated interleukin-18 levels correlated with disease activity in systemic lupus erythematosus

Abstract: The aim of this study was to determine the serum interleukin-18 (IL-18) levels in patients with systemic lupus erythematosus (SLE) and to assess their relationship with disease activity. Thirty-five patients with SLE and 35 age- and sex-matched controls were enrolled in this study. Paired serum samples were collected from all the patients with SLE, both at active stage before treatment and at the stable stage after treatment. The serum IL-18 levels were determined using ELISA and their correlations with the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
142
3
7

Year Published

2004
2004
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(170 citation statements)
references
References 23 publications
18
142
3
7
Order By: Relevance
“…Serum IL-10 levels are higher in SLE patients, and both spontaneous and mitogen-induced IL-10 production has been found to be increased in peripheral blood mononuclear cells (PBMCs) of SLE patients [24]. Furthermore, correlation of serum IL-10 levels with disease activity has been demonstrated [25,26]. In the present study, serum IL-10 levels of SLE patients were higher than normal controls.…”
Section: Discussionsupporting
confidence: 51%
“…Serum IL-10 levels are higher in SLE patients, and both spontaneous and mitogen-induced IL-10 production has been found to be increased in peripheral blood mononuclear cells (PBMCs) of SLE patients [24]. Furthermore, correlation of serum IL-10 levels with disease activity has been demonstrated [25,26]. In the present study, serum IL-10 levels of SLE patients were higher than normal controls.…”
Section: Discussionsupporting
confidence: 51%
“…The effect of IL-6 is mainly proinflammatory: the activation of IL-10 have been found to positively correlate with anti-ds DNA antibody titers and the Systemic Lupus Erythematosus Disease Activity Index (SLEDAI) and negatively with complement C3 levels. 19,20 However, in the present study, the IL-10 level in the EBC was found to correlate negatively with the activity of SLE, and it showed a similar tendency in the BALF. This finding could confirm that of Capper et al 18 regarding the coexistence of groups of SLE patients with different patterns of cytokine activity.…”
contrasting
confidence: 57%
“…31,34,35 This difference in reports could be due to the fact that non of our lupus patients had inactive disease and they all ranged from mild to severe activity with a mean SLEDAI of 13.7±4.3 which made it difficult to correlate the IL-18 level with the whole spectrum Unfortunately, similar clinical manifestations are observed among SLE patients in spite of different classes of LN, and considerable renal involvement (class III, IV, or V LN) can occur in SLE patients with insignificant proteinuria (<0.5 gm/24 hours). 36,37 Histopathological examination of the 40 renal biopsies of patients included in our study showed that two patients (5%) had class I, 12 (30%) had class II, 16 (40%) had class III, nine (22.5%) had class IV and only one patient (2.5%) had class V LN.…”
Section: Discussionmentioning
confidence: 99%